Implementasi metode Promethee Dalam Pemilihan Peminatan pada Program Studi Informatika (Studi Kasus Fakultas Ilmu Komputer Universitas Dehasen Bengkulu)”. - nedi rinaldi (INTEK : Jurnal Informatika dan Teknologi Informasi, 2022)
Dehasen University is one of the best private universities in Bengkulu City. Currently, Dehasen University provides several study programs and architecture. One of them is the Computer Science Study Program. In this study program there are several majors, one of which is the Department of Informatics. However, at this time in determining the specialization, the Faculty of Computer Science, Dehasen University does not yet have a computerized system. Specialization is still done manually by filling out specialization forms by students. Therefore, an application was built to support the student study specialization process using the Promethee method which is a ranking method that is quite simple in concept and application compared to other methods for multi-criteria analysis. This application is designed using the PHP programming language and MySQL database. The resulting system can provide convenience for the Informatics study program at the University of Dehasen Bengkulu in processing data on the selection of student specialization